(untitled) (Research, Society and Development, 2021)
The aim of this study was to discuss the role of black women regarding gender equality and the reduction of inequalities. A qualitative exploratory case study design was used through the life history method, through the narrative of the miniseries the life and history of Madam CJ Walker, produced by DeMane Davis, Eric Oberland and Lena Cordina. The miniseries tells the story of the first American to become a millionaire on her own, making her own business, earning all the money through her work, characterized by the production and sale of hair care products. It was possible to see through the reflections that by developing the capillary elixir, it showed that a black woman can effectively participate in the labor market, can occupy public spaces in the same way as men and take flight by undertaking.